Immediate effects of functional electrical orthoses in gait of hemiparetic patients - Paula, Simone de; Amorim, Pedro Henrique Carrazzoni; Reis, Alessandra Couto Cardoso (Saúde (Santa Maria), 2019)
Introduction: Functional electrical orthoses may favor ankle dorsiflexion in hemiparetic patients. Objective: The objective of this study was to evaluate the immediate effects of using the functional orthosis in the gait of hemiparetic patients. Methods: The research was performed on 10 participants with diagnosis of hemiparesis. The participants selected for this research were evaluated both with and without the use of the WalkAide® System functional electrical orthosis conducted via the 10-meter walk test and baropodometry. Results: The samples of this study were characterized by male participants averaging in age from 52,7 ± 15,3 years. The participants presented an inferior displacement time (25,64 ± 11,42 s) with the use of the functional electrical orthosis when compared to the displacement time without the orthosis (27,68 ± 12,99 s). With regards to the baropodometric data, there were significant differences in the contact area of the forefoot and the hindfoot with the use of the functional electrical orthosis. Conclusion: Functional electrical orthosis yielded immediate satisfactory results in the gait of hemiparetic patients.